Antiprotozoal Diterpenes from Perovskia abrotanoides - Tabefam, Marzieh; Farimani, Mahdi Moridi; Danton, Ombeline; Ramseyer, Justine; Kaiser, Marcel; Ebrahimi, Samad N.; Salehi, Peyman; Batooli, Hossien; Potterat, Olivier; Hamburger, Matthias (Planta Medica, 2018)
As part of a screening for new antiparasitic natural products from Iranian plants, n-hexane and ethyl acetate extracts from the aerial parts of Perovskia abrotanoides were found to exhibit strong inhibitory activity against Trypanosoma brucei rhodesiense and Leishmania donovani. The activity was tracked by high-performance liquid chromatography (HPLC)-based activity profiling. Preparative isolation by a combination of silica gel column chromatography and HPLC afforded 17 diterpenoids (1–17), including 14 abietane-, two icetexane-, and one isopimarane-type derivatives. Among these, (5R,10S)-11-hydroxy-12-methoxy-20-norabieta-8,11,13-triene (2), 12-hydroxy-norabieta-1(10),8,11,13-tetraene-1,11-furan (6), and 12-methoxybarbatusol (9) were new compounds, the structure of which was established by comprehensive spectroscopic data analysis (one- and two-dimensional nuclear magnetic resonance, high-resolution electrospray ionization mass spectrometry, electronic circular dichroism). The antiprotozoal activity of the isolated compounds was evaluated against T. b. rhodesiense, Trypanosoma cruzi, L. donovani, and Plasmodium falciparum. Selectivity indexes (SI) were calculated in comparison to cytotoxicity on rat myoblast (L6) cells. Particularly active were 7α-ethoxyrosmanol (4) with an IC50 of 0.8 µM against T. b. rhodesiense (SI 14.9) and an IC50 of 1.8 µM (SI 6.9) against L. donovani, ferruginol (8) with an IC50 of 2.9 µM (SI 19.2) against P. falciparum, and miltiodiol (10) with an IC50 of 0.5 µM (SI 10.5) against T. b. rhodesiense. None of the compounds exhibited selective toxicity against T. cruzi (SI ≤ 1.6).
Keywords: Perovskia abrotanoides; Lamiaceae; diterpenoids; Leishmania donovani; Trypanosoma brucei rhodesiense; Plasmodium falciparum